2017
DOI: 10.1111/hiv.12562
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral pill count and clinical outcomes in treatment‐naïve patients with HIV infection

Abstract: This particular single-tablet regimen is associated with a modest decrease in the risk of AIDS or death relative to multiple-pill formulations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Another finding that indicates the difficult management of these patients is the high number of concomitant medications. Indeed, while in non-advanced naïve patients we still discuss on the role of a single tablet regimen compared to more pills, the picture in late presenters is completely different [29]. Moreover, this high number of co-medications and the complex clinical picture could explain the onset of side effects that are really difficult to ascribe to a single antiretroviral drug.…”
Section: Discussionmentioning
confidence: 99%
“…Another finding that indicates the difficult management of these patients is the high number of concomitant medications. Indeed, while in non-advanced naïve patients we still discuss on the role of a single tablet regimen compared to more pills, the picture in late presenters is completely different [29]. Moreover, this high number of co-medications and the complex clinical picture could explain the onset of side effects that are really difficult to ascribe to a single antiretroviral drug.…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, in an observational study of treatment-naive patients, the estimated risk difference for virologic failure was 3.4% when taking a single tablet rather than a three-pill efavirenz-based regimen for one year. 34 In randomised trials in naïve patients or those simplifying ART, it has been difficult to show any advantage of STR over MTR with respect to virologic suppression. Since virologic failure rates are so low with all modern ART regimens, any differences are generally driven by tolerability of trial regimens.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the special requirements for consistent compatibility and effectiveness of cART, a continuing controversy concerns the safety of a substance exchange even in the case of generics with identical active ingredients [50][51][52]. Some studies have described risks for sustainability of virological control by cART when the generic drug was associated with a higher number of pills [50,53].…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the special requirements for consistent compatibility and effectiveness of cART, a continuing controversy concerns the safety of a substance exchange even in the case of generics with identical active ingredients [50][51][52]. Some studies have described risks for sustainability of virological control by cART when the generic drug was associated with a higher number of pills [50,53]. Other studies found no difference in efficacy when switching to generic drugs [51] or considered concerns to be unfounded even against multiple exchanges, as long as the bioequivalence of the prescribed generic medicines was ensured [54].…”
Section: Discussionmentioning
confidence: 99%